Complete Indian Cooking : 325 Deliciously Authentic Recipes For The Adventurous Cook - Mridula Baljekar
Choose from 325 exciting and original recipes, including delicious appetizers, main course curries, spicy side dishes and light, soothing desserts. Enjoy crisp fried vegetable samosas followed by a deliciously creamy Goan fish casserole, or a hearty leg of lamb, roasted Mughlai-style, with karahi spiced potatoes on the side. Lentil daal with roasted garlic and whole spices is just one of the many delicious vegetarian options, while a section on quick and easy Balti dishes will bring fire and spice to any mealtime.